CDK4/6 inhibition mitigates stem cell damage in a novel model for taxane‐induced alopecia. Issue 10 (12th September 2019) - Purba, Talveen S; Ng'andu, Kayumba; Brunken, Lars; Smart, Eleanor; Mitchell, Ellen; Hassan, Nashat; O'Brien, Aaron; Mellor, Charlotte; Jackson, Jennifer; Shahmalak, Asim; Paus, Ralf
Abstract: Taxanes are a leading cause of severe and often permanent chemotherapy‐induced alopecia. As the underlying pathobiology of taxane chemotherapy‐induced alopecia remains poorly understood, we investigated how paclitaxel and docetaxel damage human scalp hair follicles in a clinically relevant ex vivo organ culture model. Paclitaxel and docetaxel induced massive mitotic defects and apoptosis in transit amplifying hair matrix keratinocytes and within epithelial stem/progenitor cell‐rich outer root sheath compartments, including within Keratin 15+ cell populations, thus implicating direct damage to stem/progenitor cells as an explanation for the severity and permanence of taxane chemotherapy‐induced alopecia. Moreover, by administering the CDK4/6 inhibitor palbociclib, we show that transit amplifying and stem/progenitor cells can be protected from paclitaxel cytotoxicity through G1 arrest, without premature catagen induction and additional hair follicle damage. Thus, the current study elucidates the pathobiology of taxane chemotherapy‐induced alopecia, highlights the paramount importance of epithelial stem/progenitor cell‐protective therapy in taxane‐based oncotherapy, and provides preclinical proof‐of‐principle in a healthy human (mini‐) organ that G1 arrest therapy can limit taxane‐induced tissue damage. Synopsis: Taxane chemotherapy causes alopecia. This study shows how taxanes are toxic to dividing stem cells and transit amplifying cells in the hair follicle. A CDK4/6 inhibitor, that blocks cell division, can antagonise taxane‐induced damage in the hair follicle. Paclitaxel and docetaxel, chemotherapies that cause alopecia, promote mitotic defects and apoptosis in proliferating hair follicle stem/progenitor and transit amplifying cell compartments. Mitotic defects are marked by profound increases in phospho‐histone H3 immunoreactivity, micronucleation and transcriptional arrest. Pharmacological CDK4/6 inhibition potently induces G1 arrest in the human hair follicle. Pharmacological G1 arrest antagonises the mitosis‐targeting cytotoxicity taxanes, thereby protecting stem/progenitor cells and transit amplifying cells from damage. Abstract : Taxane chemotherapy causes alopecia. This study shows how taxanes are toxic to dividing stem cells and transit amplifying cells in the hair follicle. A CDK4/6 inhibitor, that blocks cell division, can antagonise taxane‐induced damage in the hair follicle.